Transformation to Small Cell Lung Cancer as an Acquired Resistance Mechanism in EGFR-mutant Lung Adenocarcinoma: A Case Report of Complete Response to Etoposide and Cisplatin. Issue 3 (May 2015) - Hwang, Ki-Eun; Jung, Jae-Wan; Oh, Su-Jin; Park, Mi-Jeong; Shon, Young-Jun; Choi, Keum-Ha; Jeong, Eun-Taik; Kim, Hak-Ryul
First-line epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) for patients with advanced non-small cell lung cancer who were selected on the basis of EGFR mutations have improved the progression-free survival with acceptable toxicity compared to standard chemotherapy. However, acquired resistance to EGFR-TKIs has been identified as an important clinical problem. Transformation to small cell lung cancer (SCLC) is a rare mechanism of resistance to EGFR-TKI therapy. We describe the case of a 61-year-old man who presented transformation from adenocarcinoma to SCLC as the manifestation of acquired resistance after EGFR-TKI treatment. He underwent chemotherapy with etoposide and cisplatin and achieved a complete response.